2014
DOI: 10.7860/jcdr/2014/9988.5196
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Monotypic Plasma Cells with Absence of Neoplastic B Cell Component in a Treated Case of Waldenström Macroglobulinemia: A Sign of Residual Disease?

Abstract: A 57-year-old male, known case of chronic inflammatory demyelinating polyneuropathy with POEMS Syndrome (Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes) presented with generalized weakness. Peripheral blood smear findings were within normal limits. Bone marrow smears showed mild increase in lymphoid cells including many lymphoplasmacytoid cells and increased in plasma cells. Bone marrow biopsy revealed hypercellular marrow spaces with small and large lymphoid aggregates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Distinguishing the clonal cells in WM patient and their molecular characterization is important step for treatment and subsequent detection of the residual cell clone after clone′s specific therapy. Studies detecting the residual monotypic plasma cells in WM sample after treatment by anti‐B cell–specific antibodies were published …”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing the clonal cells in WM patient and their molecular characterization is important step for treatment and subsequent detection of the residual cell clone after clone′s specific therapy. Studies detecting the residual monotypic plasma cells in WM sample after treatment by anti‐B cell–specific antibodies were published …”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous composition of the bone marrow infiltration in WM, including variable percentages of small lymphocytes, plasmacytoid lymphocytes, and plasma cells [ 101 ], is also amenable to study at the single-cell level. The pathophysiology of the plasma cell involvement is poorly understood, and it has been observed that residual plasma cells may be present even in the complete response when the neoplastic B-cell component is absent [ 102 , 103 ]. Moreover, according to a recent study, concordance between the mutational landscape of WM B-cells and plasma cells is not 100%, suggesting that not all WM B-cells differentiate into plasma cells [ 69 ].…”
Section: Single-cell Techniques In Waldenström’s Macroglobulinemiamentioning
confidence: 99%